A CASE STUDY OF FRAUD IN THE KARANGANYAR DISTRICT COURT (Verdict Number:159/Pid.B/2019/PN Krg) - Perdana, Dian (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The theoretical benefits of this research are expected to be able to contribute to legal science, especially criminal law and also those who have an interest in conducting research on criminal acts of fraud and are practically expected to provide benefits to development in the field of law and legal awareness of society in general. This research is theoretically expected to contribute to the development of legal science, especially criminal law and also those who have an interest in conducting research on criminal acts of fraud and are practically expected to provide benefits to development in the field of law and public legal awareness in This research was conducted with the type of normative legal research carried out by literature study of legal materials, both primary legal materials, secondary legal materials, and tertiary legal materials and / or non-legal materials, while the analysis method was carried out by collecting data which were then linked to existing problems are arranged systematically and logically, so that a research result is obtained on the Criminal Case Study of Fraud in the Karanganyar District Court (Decision Number 159 / Pid.B / 2019 / Pn Krg) Based on the results of the research, it is concluded that, the defendant was charged with alternative charges by being legally proven and convincingly guilty of committing a criminal act of fraud as regulated in Article 378 of the Criminal Code, it is appropriate and has been based on facts at trial, valid evidence. in the form of witness statements, evidence, letters in the form of a statement letter, and statements from the defendant. The defendant was sentenced to 1 year imprisonment Keywords: fraud, alternative indictmen.